2011
DOI: 10.1002/pssc.201084053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(3, 4 ethylenedioxythiophene) nano structure using reverse microemulsion polymerization

Abstract: We have synthesized Poly (3,4 ethylenedioxythiophene) (PEDOT) nanostructured powder through a hexane/water reverse microemulsion system using sodium bis(2‐ethylhexyl) sulfosuccinate (AOT) cylindrical micelles as the template and ferric chloride (FeCl3) as the oxidant. Infrared spectroscopic study revealed that the polymerization of ethylenedioxythiophene leads to formation of the polymer PEDOT. The morphology of particles were studied using scanning electron microscopy (SEM) which showed nanometer sized agglom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…8,9 Based on these conventional methods, numerous studies were carried out to optimize, to structuralize and to functionalize CPs. 10 For this purpose, reverse micro-emulsion polymerization 11,12 and CP composites with carbon nanotubes (CNTs) 13,14 have been employed to produce polymer nanotubes, 15,16 wires, 17 nanorods, 18 fibers, 19 etc. Furthermore, polymer-metal oxide nanocomposites were used to enhance their thermal, mechanical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Based on these conventional methods, numerous studies were carried out to optimize, to structuralize and to functionalize CPs. 10 For this purpose, reverse micro-emulsion polymerization 11,12 and CP composites with carbon nanotubes (CNTs) 13,14 have been employed to produce polymer nanotubes, 15,16 wires, 17 nanorods, 18 fibers, 19 etc. Furthermore, polymer-metal oxide nanocomposites were used to enhance their thermal, mechanical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured materials, including nanofibers, 23 nanowires, 24 nanorods, 25 nanoflowers, 26 nanotubes 27 and so on, have been widely applied in energy storage and other fields, especially supercapacitors, because they can provide high surface area and porosity, which lead to higher charge/discharge capacity. 28 For example, Li et al reported the specific capacitance of nanostructural PEDOT was 109.11 F g −1 at 1 A g −1 , which was significantly higher than that of traditionally structured PEDOT (69 F g −1 at 0.2 A g −1 ) as reported by Zhao et al 29,30 Among different nanomaterials, nanotubes can greatly contribute to electrochemical performance owing to their available internal and external surface areas. The morphology of nanotubes provides significant advantages for ion transport and reduces the diffusion distance.…”
mentioning
confidence: 92%
“…Conductive fibers based on conducting polymer have been investigated from both fundamental and technological aspects to understand their electrical and mechanical properties and practical use for electromagnetic interference shielding, conducting textiles, and organic electronics [1][2][3][4][5] .It was reported that conductive PANI-DBSA/Co-PAN fibers could be obtained with wet-spinning process from a solution of dodecilbenzenesulphonic acid doped PANI and PAN prepared in dimethylformamide. The conductivity of the fibers having 7 wt% PANI-DBSA reached to a value of 10 -3 S/cm and the tensile strength of the fibers was in the range of 2.5 to 3.5 cN/dtex [6] .…”
Section: Introductionmentioning
confidence: 99%